النزاعات داخل المنظمات غير الربحية - (:unkn) unknown (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة الى معرفة هل التنظيم الاداري والقانوني لعمل الجمعيات الدينية المسجدية كفيل للحد من اسباب الصراعات الداخلية والخارجية؟ وقد استخدمنا تقنية المقابلة التي تدخل ضمن المنهج الكيفي وتم اختيار العينة بطريقة قصدية وتوصلنا الى النتائج التالية: ان تحقيق السلم المؤسسي داخل المساجد لا يكون بالقانون وحده، ولا بالتنظيم وحده، بل بمنظومة متكاملة تنطلق من الفهم والتكوين والتفعيل، وتصبّ جميعها في خدمة رسالة المسجد كمؤسسة جامعة، وليست ساحة خلاف. Thesis Title: The Work of Non-Profit Organizations – A Case Study of Approved Religious Associations This study aims to determine whether the administrative and legal framework governing the work of mosque-based religious associations is sufficient to reduce the causes of internal and external conflicts. We employed the interview technique, which falls under the qualitative approach, and the sample was selected intentionally. The following results were obtained: The achievement of institutional peace within mosques is not attained through law alone, nor through organization alone, but rather through an integrated system that begins with understanding, formation, and activation, all of which contribute to serving the mission of the mosque as a unifying institution, not a space of conflict.
حالة الجمعيات الدينية المعتمدة لدى مديرية الشؤون الدينية و الاوقاف مستغانم
Keywords: التنظيم الاداري،الصراع،المنظمة غير الربحية،الجمعيات الدينية،العمل التطوعي،المسجد